Plaque assay of avian sarcoma viruses using casein. - Balduzzi, P C (1975)
The caseinolytic activity of several strains of Rous sarcoma virus (RSV), conditional and nonconditional mutants of RSV, and nontransforming avian leukosis viruses was investigated. Only those viruses capable of transforming chick fibroblasts in vitro induced lysis of casein incorporated into an agar overlay. Lysis produced distinct clear areas in the turbid casein-agar gel which allowed a quantitative "plaque" assay of cell transformation. Casein plaque formation could not be separated from morphological conversion in cultures infected by wild-type RSV strains. In plates infected by mutants temperature sensitive for transformation, the caseinolytic activity appeared to be affected by temperature to a lesser extent than morphological conversion.